Choriocapillaris flow deficits in normal Chinese imaged by swept-source optical coherence tomographic angiography - Cheng, Weijing; Song, Yunhe; Lin, Fengbin; Jin, Ling; Wang, Zhenyu; Jonas, Jost B.; Wang, Wei; Zhang, Xiulan (American journal of ophthalmology, 2022)
Purpose - To evaluate the ocular and systemic determinants of the choriocapillaris flow deficits percentage (CC FD%) in normal eyes. - Design - Observational cross-sectional study. - Methods - Healthy Chinese participants without ocular or systemic diseases underwent detailed ophthalmic evaluations, including swept-source optical coherence tomography angiography (SS-OCTA) with 6- × 6-mm macular choriocapillaris images. The CC FD% was assessed in circular regions with diameters of 1.0 and 5.0 mm, rings with 1.0- to 2.5-mm diameters, and rings with 2.5- to 5.0-mm diameters. - Results - The study included 830 individuals (mean ± SD age 58.66 ± 8.75 years). CC FD% (mean ± SD 22.05% ± 1.13%) was the lowest in the 2.5- to 5.0-mm ring, followed by the 1.0- to 2.5-mm ring, and highest in the 1.0-mm circle. In multivariable analysis, a higher CC FD% was associated with older age (β = 0.16 [95% confidence interval CI] 0.08-0.24, P < .001), higher intraocular pressure (β = 0.34 [95% CI 0.25-0.42], P < .001), higher serum concentrations of high-density lipoprotein cholesterol (β = 0.24 [95% CI 0.17-0.32], P < .001), and lower image quality score (β = −0.22 [95% CI −0.30 to −0.14], P < .001). CC FD% was also independent of axial length. - Conclusions - In healthy adult Chinese individuals, a higher CC FD% was associated with older age, higher intraocular pressure, and higher high-density lipoprotein cholesterol serum concentration. These factors may influence clinical assessments of the choriocapillaris. The lack of an association between CC FD% and axial length is consistent with similar findings for Bruch membrane thickness, macular retinal thickness, and macular retinal pigment epithelium cell density.
Online verfügbar: 25. September 2021, Artikelversion: 11. Dezember 2021
Gesehen am 09.04.2024